Efficacy and safety of early soluble urokinase plasminogen receptor plasma-guided anakinra treatment of COVID-19 pneumonia: a subgroup analysis of the SAVE-MORE randomised trial. (February 2023) - Akinosoglou, Karolina; Kotsaki, Antigone; Gounaridi, Ioanna-Maria; Christaki, Eirini; Metallidis, Simeon; Adamis, Georgios; Fragkou, Archontoula; Fantoni, Massimo; Rapti, Aggeliki; Kalomenidis, Ioannis; Chrysos, Georgios; Boni, Gloria; et al.
Summary: Background: The SAVE-MORE trial demonstrated that anakinra treatment in COVID-19 pneumonia with plasma soluble urokinase plasminogen activator (suPAR) levels of 6 ng/mL or more was associated with 0.36 odds for a worse outcome compared to placebo when expressed by the WHO-Clinical Progression Scale (CPS) at day 28. Herein, we report the results of subgroup analyses and long-term outcomes. Methods: This prospective, double-blind, randomised clinical trial, recruited patients with a confirmed SARS-CoV-2 infection, in need of hospitalisation, lower respiratory tract infection and plasma suPAR ≥6 ng/mL from 37 academic and community hospitals in Greece and Italy. Patients were 1:2 randomised to subcutaneous treatment with placebo or anakinra (100 mg) once daily for 10 days. Pre-defined subgroups of Charlson's comorbidity index (CCI), sex, age, level of suPAR, and time from symptom onset were analysed for the primary endpoint (overall comparison of distribution of frequencies of the scores from the WHO-CPS between treatments on day 28), by multivariable ordinal regression analysis in the intention to treat (ITT) population. This trial is registered with the EU Clinical Trials Register (2020-005828-11) and ClinicalTrials.gov (NCT04680949). Findings: Patients were enrolled between 23 December 2020 and 31 March 2021; 189 patients in the placebo arm and 405 patients in the anakinra arm were the ITT population. Multivariable analysis showed that anakinra treatment was accompanied by significantly lower odds for worse outcome compared to placebo at day 28 for all studied subgroups (CCI ≥ 2, OR: 0.34, 95% confidence intervals [CI] 0.22–0.50; CCI < 2, OR: 0.38, 95% CI 0.21–0.68; suPAR > 9 ng/mL, OR: 0.35, 95% CI 0.19–0.66; suPAR 6–9 ng/mL, OR: 0.35, 95% CI 0.24–0.52; patients ≥65 years, OR: 0.41, 95% CI 0.25–0.66; and patients <65 years, OR: 0.29, 95% CI 0.19–0.45). The benefit was uniform, irrespective of the time from start of symptoms until the start of the study drug. At days 60 and 90, anakinra treatment had odds of 0.40 (95% CI 0.28–0.57) and 0.46 (95% CI 0.32–0.67) respectively, for a worse outcome compared to placebo. The costs of general ward stay, ICU stay, and drugs were lower with anakinra treatment. Interpretation: Anakinra represents an important therapeutic tool in the management of COVID-19 that may be administered in all subgroups of patients; benefits are maintained until day 90. Funding: Hellenic Institute for the Study of Sepsis ; Swedish Orphan Biovitrum AB .